WEB DESIGN APPLICATIONS FOR MARKETING IN DISTRO PELANGI USING PHP, MYSQL, AND MACROMEDIA DREAMWEAVER 8 - Prima Yuningsih; Eriek Orlando (Jurnal Sistem Informasi, 2010)
Nowadays there are so many distibutor outlet (Distro) in either big or smalltown. The concept may very detends on demand of the fashion vogue. Howeverthe large number of distro become a fierce competition for the teller. Thereforemarketing and product promotion are very important and would be better is thepromotion can widely and easily read by every person. Website is the easiestway which can fulfill that case by using PHP programming, MySQL Database ,and macromedia Dreamweaver 8. With the website design applications on distropelangi its extected that it can give the consumers to get informations of theexisting product on distro pelangi, so that is can increase the sales number ondistro pelangi.